IMPLIKASI PROFESIONALISME DAN KUALITAS ETOS KERJA TENAGA PENDIDIK (GURU) TERHADAP PENINGKATAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH AL-ANWAR DESASAMPIRAN TAHUN CIREBON 2019 - Dwi Suryanto; Karsono Karsono (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study are: 1) To determine the effect of professionalism on improving the quality of education in Madrasah Tsanawiyah AL-Anwar Village, Saitan Talun Cirebon 2019. 2) To determine the effect of the work ethic quality of educators (teachers) on improving the quality of education in Madrasah Tsanawiyah AL- Anwar Desa Saitan Talun Cirebon 2019. 3) To find out the influence of professionalism and work ethic quality of teaching staff (teachers) together to improve the quality of education in Madrasah Tsanawiyah AL-Anwar Sanggar Talun Village Cirebon 2019. This research is quantitative, descriptive and associative type. The population in this study were 40 people in the teachers and staff at Madrasah Tsanawiyah AL-Anwar Village of Saitan Talun Cirebon 2019. In this study the sampling technique used saturated sampling (census). The respondents that I use as many as 40 respondents, namely teachers and employees at Madrasah Tsanawiyah AL-Anwar Village, Sleting Talun Cirebon 2019.